Bangladesh Pediatric Association e-shishu Framework: A proposal for the development of an integrated service (Northern International Medical College Journal, 2025)
To keep pace with the increasingly technological advent around the world Bangladesh needs to develop technologies that support the care of children addressing issues related to growth and development, children's changing physiology, and the unique diseases of children and interventions of pediatric care. Connectivity and data integration are particular concerns for child health care workers. Consumer health information needs for this population extend beyond the needs of one individual to the needs of the family. In this proposal we chalked out a complete IT-enabled framework incorporating parents, pediatricians and general viewers to meet the healthcare needs. This proposed framework will be centralized, database driven service. It will include a core website, desktop and mobile application for the parents and also for the pediatrician. The main benefit is the centralized storage of huge data. Parents will be benefited by storing their children’s anthropometric data, as well as prescription. Pediatricians will also be able to create and transmit prescription virtually as well as have the opportunity to use this data for research and planning. Last of all the pediatric association will have the complete data regarding the pediatricians, the children, disease particulars as well.Northern International Medical College Journal Vol. 14 No. 1-2 July 2022-January 2023, Page 605-608